To solve the equation \((x + 4)^2 = 4\) using the square root property, we can first take the square root of both sides. The square root property states that if \(a^2 = b\), then \(a = \sqrt{b}\) or \(a = -\sqrt{b}\).
-
Start with the equation: \[ (x + 4)^2 = 4 \]
-
Apply the square root property: \[ x + 4 = \sqrt{4} \quad \text{or} \quad x + 4 = -\sqrt{4} \]
-
Since \(\sqrt{4} = 2\), we have: \[ x + 4 = 2 \quad \text{or} \quad x + 4 = -2 \]
-
Solve each equation:
-
For \(x + 4 = 2\): \[ x = 2 - 4 \implies x = -2 \]
-
For \(x + 4 = -2\): \[ x = -2 - 4 \implies x = -6 \]
-
Thus, the solutions are: \[ x = -2, -6 \]
In conclusion, the solution(s) is/are: \[ \boxed{-2, -6} \]